A Concise Synthesis of the Erythrina Alkaloid 3–Demethoxyerythratidinone via Combined Rhodium Catalysis - Joo, Jung Min (2010)
[Image: see text] The total synthesis of the erythrina alkaloid 3–demethoxyerythratidinone has been achieved via a strategy based on combined rhodium catalysis. The catalytic tandem cyclization effected by the interplay of alkynyl and vinylidene rhodium species allows for efficient access to the A and B rings of the tetracyclic erythrinane skeleton in a single step. The synthesis also features rapid preparation of the requisite precursor for the double ring closure and thus has been completed in only 7 total steps in 41% overall yield.